INFLUENCE OF AIR-DECK LENGTH ON FRAGMENTATION IN QUARRY BLASTING - Suttithep Rommayawes; Chewchan Leelasukseree; Pirat Jaroonpattanapong (European Scientific Journal, ESJ, 2014)
An air gap in the explosive column known as an air deck has been applied in open-pit blasting as a means to reduce explosive charge, vibration, fly rock, and improve fragmentation and controlled blasting in some situations. Determining the appropriate airdeck length and optimum fragmentation is still in question despite many applications and studies. In this research, a total of 30 air-deck blasts with air-deck lengths between 15-65% of the charge length were tested while also considering two other important parameters: maximum joint spacing and blasting direction. Average fragmentation size was obtained from image processing analysis and used as an indicator of blasting performance. Results indicate that the average fragmentation size increases relative to the higher percent air-deck length and maximum joint spacing. In addition, an unfavorable blasting direction also increases average fragmentation size. The relationship between average fragmentation size and an air-deck length is displayed on a graph for simplicity of uses. The small to medium opening feed size of a normal primary crusher may vary between 93cm (37 inches) to 112cm (44 inches) so an air-deck length between 20-30% of the charge length can be used with a high possibility that the average fragmentation size will be less than 100cm. With favorable parameters, an air-deck length of up to 40% is worth testing in the quarry mines; however, other uncontrollable parameters exist and may also affect blast fragmentation.